Language Socialization between Two Different Non-Native English Speakers through Conversation Analysis - Saputra, Eko (Yayasan Sembilan Pemuda Indonesia, 2022)
This paper presents evidence that there are, at least, three important language socialization phenomena within a dyadic Non-Native English Speaker (NNES) conversation. By doing conversation analysis of the two NNES in a non-formal situation, it is found that; (1) Background knowledge cannot be separated from the language acquisition process in mediating the discovery of a new concept (2) The value of tolerance owned by more expert individual contributes positively to the success of new member learning process and (3) Socialization process earned not only through direct experience but also an indirect process that may still give the same impact for the readiness of a potential new member before actually engaging in a community.